Pengaruh Aplikasi C# dalam Proses Perhitungan Numerik Terhadap Solusi Persamaan Non Linier - Yahya Yahya; Amri Mulyawan Nur (Infotek: Jurnal Informatika dan Teknologi, 2018)
The solution in the process of completing numerical methods, especially "Non-Linear Equation Solutions", is determined by several criteria including: 1. Solutions will be obtained if tolerance found from the calculation results is numerically smaller or equal to the specified tolerance, depending on the criteria of the problem. 2. The solution will be obtained if the function value f (xn + 1) reaches zero (0). 3. The solution will be obtained if the xn + 1 value has a constant value (no changes). In several observations of non-liner equations, which are done manually, students cannot do it perfectly. This is due to the level of understanding of teaching materials or modules and algorithms used to experience difficulties, especially for several iterations in order to obtain the expected results. From the results of calculations that are done manually, using Microsoft Excel and using numerical applications that are made using the C # programming language, the results are found, among others: manual calculation of non-linear equations to get one of the roots of non-linear functions tends to be resolved in a short time so that the error rate and accuracy cannot be measured, Calculations made using Microsoft Excel, obtained an error rate of 0.158% and an accuracy rate of 99.842%. Calculations made using numerical applications using the C # programming language obtained an error rate of 0.004% and an accuracy rate of 99.996%DOI : 10.29408/jit.v1i2.901